Application of artificial intelligence technology in the field of security vulnerability - Hongyu SUN; Yuan HE; Jice WANG; Ying DONG; Lipeng ZHU; He WANG; Yuqing ZHANG (Tongxin xuebao)
The large number of software and the enhancement of complexity have brought severe challenges to the research of software security vulnerabilities.The efficiency of manual research on security vulnerabilities is low and cannot meet the needs of cyberspace security.Therefore,how to apply artificial intelligence techniques such as machine learning and natural language processing to the study of security vulnerabilities has become a new hot spot.Artificial intelligence technology can intelligently process vulnerability information,which can assist in the research of security vulnerabilities and improve the efficiency of research on security vulnerabilities such as vulnerability mining.Firstly,the key technologies of automatic mining,automatic assessment,automatic exploitation and automatic repair of security vulnerabilities were analyzed,which pointed out that the automation of security vulnerability mining was the key of the application of artificial intelligence in the field of security vulnerability.Then,the latest research results of applying artificial intelligence technology to the research on security vulnerabilities was analyzed and summarized in recent years,which pointed out some problems in the application and gave corresponding solutions.Finally,the development trend of intelligent research on security vulnerabilities was prospected.